Analysis of Sources of Occupational Stress Among Teachers and Educational Support Specialists - Vaitkevičienė, Asta; Alifanovienė, Daiva; Kepalaitė, Albina (Special Education, 2023)
The article analyses the data of an empirical study revealing the contexts of sources of occupational stress for teachers and educational support specialists. In order to analyse the experience of specialists, a questionnaire was compiled, the statements of which were formulated on the basis of the analysis of scientific (theoretical and empirical) research on occupational stress.N=205 respondents were surveyed with this questionnaire. Referring to the data from the exploratory and confirmatory statistical analyses of the survey data in the context of this sample, a final questionnaire suitable for use in the study of stressogenic sources of teachers and educational support specialists was constructed. Statistically significant relationships between sources of occupational stress were also revealed.